Environmental compatibility of sand replenishment in the surf zone off the Island of Sylt, 2009-2010 - Werner Armonies; Christian Buschbaum (PANGAEA, 2010)
For coastal protection, the longshore bar in the surf zone off the western shore of the island of Sylt was replenished in summer 2009. Some 300-400 m^3 of sand were dumped per m of coastline. We studied (1) the faunal composition of macrobenthos in the breaker zone along the island of Sylt, and (2) the effects of sand dumping on macrobenthos (a) after 9 months (before - after sampling design), and (b) after four years (comparison of replenished and neighboring non-replenished sites). The longshore bar consists of coarse sand, but medium and even fine sand can be found where the bar is eroded. These differences in sediment composition cause faunal heterogeneity on a small spatial scale (100s of m) while the fauna is rather homogeneous on larger (km to 10s of km) scales. During sand replenishment, the eroded sites with fine and medium sand were covered with coarse sand. This caused a loss of fine- and medium sand species and the number of benthic species decreased accordingly. After one year, macrobenthos abundance and biomass did not differ between replenished and control sites. After four years, species number and species identity had levelled out as well. The longshore bars typically experience strong turbulence with frequent sediment disturbance and the fauna living there need to be adapted. Sand replenishment turned out to be a disturbance equivalent to the natural ones and therefore did not change the coarse sand fauna.